P1492HUMAN FACTORS TESTING OF THE QUANTA SC+: DEMONSTRATING EASE OF USE WITH MINIMAL UPFRONT TRAINING IN HEALTH CARE PRACTITIONERS AND PATIENTS. (6th June 2020) - Compton, Kathryn; Edwards, Christian; Komenda, Paul; Bose, Amit; Milad, John
Abstract: Background and Aims: Quanta Dialysis Technologies has developed a compact, powerful personal haemodialysis system intended for home and self-care use designed in collaboration with patients and healthcare practitioners. Human factors testing is necessary to demonstrate ease of use with minimal up-front training. Method: In compliance with FDA guidance and EU standards, the user interface of the system was evaluated through human factors testing to assess the safe and effective use of SC+. This included a series of user-based tasks whereby representative users independently setup SC+ into a simulated treatment, managed alarms to resolution and external SC+ cleaning/disinfection. All participants received an introduction to SC+ and completed a competency sign off at the end of training. 17 healthcare professionals (6 renal nurses, 8 dialysis technicians, 1 patient care technician) received up to 4 hours of structured training followed by a 1-day learning decay period. In addition, 10 lay users (8 dialysis patients, 2 caregivers) received between 5.5 and 7.5 hours training followed by a 2-day learning decay period. Results: Between the two user groups, there were a total of 8, 110 opportunities for use errors to occur. Despite minimal training and representative learning decay, only 4 significant use events were observed requiring some user manual enhancements. Other use errors captured were minor or could not be mitigated further due to clinical practices and shared inherent risks across all haemodialysis systems. Conclusion: The results of the human factors testing demonstrated that healthcare practitioners, patients and caregivers successfully operated SC+ independently with a high level of use safety, despite minimal training and learning decay. The SC+ user interface is optimized for safe and effective use under FDA guidance and EU standards.